“The Resident of Irrigation”: Notes of Hendrik Altmann as Resident of Kediri in Memori van Overgave, 1919 - Kusairi, Latif (MOZAIK HUMANIORA, 2025)
This writing explores the records of the Resident of Kediri in 1919, as documented in the Memori van Overgave of Resident H. Altmann. He observed several irregularities in the water   channels, particularly in the Brantas River. In this memorandum, a report was submitted to the East Java Office concerning the management of Brantas River irrigation, which was coordinated by the Irrigatie Afdeling Brantas (IAB). The IAB was headquartered in Mojokerto and had a representative office in Pare, Kediri. In his presentation, the Resident of Kediri expressed significant frustration with the irrigation system of the Brantas River. This was due to the large amount of sand entering the river from mountainous areas. Additionally, there was growing concern that poor maintenance of the Brantas River’s flow could disrupt waterway transportation, which served as a key economic route connecting downstream regions. The excessive sand in the river could lead to sedimentation causing the riverbed to become shallow. As a result, during his tenure, Hendrik Altmann frequently complained about the poor state of the water channels, considering the Brantas River’s crucial role as a trade route. On the other hand, inadequate management of the river hindered economic activities in the Kediri region. Analyzing this memorandum reveals that environmental issues in the Kediri Residency were extensive—not only the eruption of Mount Kelud but also its aftermath. The volcanic materials deposited in the river led to sedimentation, which subsequently caused flooding, especially in the Kediri Residency area.